Determinan Kecenderungan Fraud Di Era Pandemi Covid19 Yang Dimoderasi Budaya Tri Hita Karana - A.A. Made Citra Adelia; Edy Sujana; I Gusti Ayu Purnamawati (JIMAT (Jurnal Ilmiah Mahasiswa Akuntansi) Undiksha, 2023)
Abstract The weakening of the economic sector has an impact on the number of Fraud cases that occur. This study aims to examine and analyze the effect of compensation suitability, situational leadership style, individual morality, and Whistleblowing on Fraud tendencies in the COVID-19 pandemic era, as well as to examine and analyze the suitability of compensation, situational leadership style, individual morality, and Whistleblowing moderated by culture. Tri hita karana against the tendency of Fraud in the era of the COVID-19 pandemic. The population in this study were employees at RSIA Harapan Bunda, amounting to 49 people. This study uses a saturated sample, which means that the entire population is sampled. The data in the study were collected through a questionnaire method. The analytical method used is MRA using the SPSS 22 program. This study uses the theory of Fraud pentagon and attribution theory. The results showed that the suitability of compensation, situational leadership style, individual morality, and Whistleblowing had a significant negative effect on the tendency of Fraud, and the tri hita karana culture was able to moderate the effect of the suitability of compensation, situational leadership style, individual morality, and Whistleblowing on the tendency of Fraud.   Keywords : thk culture, tendency fraud, COVID-19